2006
DOI: 10.1063/1.2222084
|View full text |Cite
|
Sign up to set email alerts
|

Slice imaging and velocity mapping using a single field

Abstract: A 4D wave packet study of the CH3I photodissociation in the A-band. Comparison with femtosecond velocity map imaging experiments J. Chem. Phys. 135, 154306 (2011); 10.1063/1.3650718 Conformer specific dissociation dynamics of iodocyclohexane studied by velocity map imaging J. Chem. Phys. 135, 094312 (2011); 10.1063/1.3628682Determining the CH 3 SO 2 → CH 3 + SO 2 barrier from methylsulfonyl chloride photodissociation at 193 nm using velocity map imagingIn this study we demonstrate that it is possible to perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 21 publications
2
66
0
Order By: Relevance
“…We used delayed pulsed extraction slicing 50 in the single field configuration developed by Kitsopoulos and Papadakis and described in detail in Ref. 51. Briefly, the delayed pulsed extraction allows the ion cloud to spread in velocities so that the arrival time of the ion packet at the detector has a width of several hundreds of nanoseconds.…”
Section: Methodsmentioning
confidence: 99%
“…We used delayed pulsed extraction slicing 50 in the single field configuration developed by Kitsopoulos and Papadakis and described in detail in Ref. 51. Briefly, the delayed pulsed extraction allows the ion cloud to spread in velocities so that the arrival time of the ion packet at the detector has a width of several hundreds of nanoseconds.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Alternatively, Papadakis and Kitsopoulos have shown that the arrangement can be simplified using only two specifically shaped electrodes to generate the desired electrostatic lens and a single field. 12 Although differa) j.r.r.verlet@durham.ac.uk.…”
Section: Introductionmentioning
confidence: 99%
“…However, images were also recorded (not shown) using a perpendicular polarization set-up of both lasers in order to check the detector response as well as the possible rotational angular momentum alignment of the fragment. The CH 3 + images are recorded using our VMI apparatus in the single-field configuration [29,30]. [31], prior to extracting the translational energy and angular distributions.…”
Section: Methods (A) Experimentalmentioning
confidence: 99%